Modified emulsified asphalt and preparation method thereof
Modified emulsified asphalt was prepared by using composite modifiers and gradient shear strategies, which solved the problems of modifier compatibility and storage stability, improved the high-temperature stability, low-temperature crack resistance and storage period of emulsified asphalt, met the usage requirements of high-grade highways, and reduced production energy consumption and maintenance costs.
Patent Information
- Application Number
- CN202610193360.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-10
- Publication Date
- 2026-05-26
Smart Images

Figure CN122080439A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of emulsified asphalt technology, specifically a modified emulsified asphalt and its preparation method. Background Technology
[0002] Emulsified asphalt is not only used for tack coat, primer coat, and seal coat construction on new highways, but also extensively applied in micro-surfacing, slurry seal, and crack repair projects for existing roads. To further improve the road performance of emulsified asphalt to meet the demands of heavy traffic, complex climatic conditions, and long service life on high-grade highways, modification technology has become a core direction in the research and application of emulsified asphalt. However, existing modified emulsified asphalt preparation technologies still face the following technical challenges: Existing modifiers generally have poor compatibility with asphalt matrix. Most preparation processes require high-temperature, long-term stirring to promote mixing. This process not only significantly increases energy consumption and production costs but also easily leads to thermal degradation of the modifier, destroying its original modifying function. The direct consequence is that the high-temperature stability and low-temperature crack resistance of emulsified asphalt cannot be simultaneously met. In the high-temperature environment of summer, it is prone to rutting and shoving, while in the low-temperature environment of winter, it is prone to shrinkage cracks, failing to meet the stringent requirements of high-grade highways for load-bearing capacity, deformation resistance, and fatigue resistance.
[0003] Existing emulsified asphalt exhibits poor storage stability. During static storage and long-distance transportation, it is highly susceptible to asphalt particle segregation, flocculation, and even sedimentation, resulting in a generally short effective storage period, typically not exceeding three months. To mitigate this issue, the industry often employs the addition of large amounts of stabilizers. However, excessive stabilizer introduction significantly reduces the adhesion between emulsified asphalt and aggregates, leading to weak bonding between the paved road surface and base course. This, in turn, reduces the overall strength, durability, and water resistance of the road, shortens its service life, and increases subsequent maintenance costs. Summary of the Invention
[0004] The purpose of this invention is to provide a modified emulsified asphalt and its preparation method to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing modified emulsified asphalt, comprising the following specific steps: Preferably, in the raw material pretreatment stage, 70 parts of base asphalt are selected and placed in a heating kettle equipped with a vacuum devolatilization device. The mixture is kept at a constant temperature of 125-135℃ and a vacuum of -0.06~-0.08MPa for 35 minutes to accelerate the removal of moisture and light volatiles, and finally obtain pretreated asphalt.
[0006] 5.5 parts of a composite modifier were selected, consisting of 3 parts epoxy-modified styrene-butadiene rubber latex, 2 parts graphene oxide-silica hybrid, and 0.5 parts modified polyvinyl alcohol. The graphene oxide-silica hybrid was prepared by covalent bonding using KH-550 silane coupling agent. The graphene oxide had a 1-5 layer sheet structure, with a carbon content of 68%-85wt%, an oxygen content of 15%-30wt%, a lateral size of 100-500nm, and metallic impurities of Fe≤0.05% and Cu≤0.02%, ensuring the hybrid reaction activity and dispersion uniformity. When preparing the pre-dispersion of the composite modifier, the graphene oxide-silica hybrid was first added to 10... The mixture is ultrasonically dispersed in deionized water for 20 minutes, then epoxy-modified styrene-butadiene rubber latex and modified polyvinyl alcohol are added, and stirring is continued for 20 minutes. The mixture is then placed in a mixing tank and stirred at 65°C and 900 r / min for 20 minutes to form a stable pre-dispersion of the modifier. Through the reaction of epoxy groups with the active sites of asphalt and the layered support structure of the hybrid, the synergistic effect of flexible reinforcement and rigid support is enhanced. Prepare an aqueous solution of 12 parts emulsifier, consisting of 2 parts cationic emulsifier, 0.3 parts penetration enhancer, and 9.7 parts deionized water, and stir until transparent at 55°C.
[0007] High-speed shearing operation: Shear at 3000-4000 r / min for 5-8 minutes, and keep the material temperature stable at 60-70℃ during shearing to ensure uniform material dispersion.
[0008] Ultrasonic dispersion: Set the ultrasonic power to 280-320W and disperse continuously for 15-25 minutes until there is no obvious particle aggregation in the system.
[0009] The preparation process of the graphene oxide-silica hybrid is as follows: Graphene oxide and silica are weighed at a mass ratio of 1:0.8-1.2, and 10-15 times their mass of anhydrous ethanol is added. The mixture is ultrasonically dispersed for 10-15 minutes at an ultrasonic dispersion power of 280-320W. KH-550 silane coupling agent is diluted with anhydrous ethanol at a ratio of 1:1. After dilution, it is slowly added dropwise at a rate of 1-2 drops / second, while maintaining stirring during the addition process to ensure uniform coupling reaction. 5%-8% of the mass of KH-550 silane coupling agent of graphene oxide is added dropwise, and the mixture is stirred at 70-80℃ and 300-500 r / min for 2-3 hours. After the reaction, the mixture is centrifuged, and the precipitate is vacuum dried at 60-80℃ for 8-12 hours and then ground through a 200-mesh sieve to obtain the final product.
[0010] Preferably, in the modified premixing stage, the prepared modifier predispersant liquid is slowly added to the pretreated asphalt, the feeding rate is controlled at 0.8 parts / min, and the asphalt temperature is maintained at 135-140℃.
[0011] Turn on the high-speed shearing machine and adopt a gradient shearing strategy. First, shear at 2500 r / min for 10 min for initial dispersion. Then, raise the temperature to 140-145℃ and shear at 3500 r / min for 15 min. The high shear force refines the micro agglomerates. At the same time, add 0.2 parts of accelerator to accelerate the bonding of epoxy modified styrene-butadiene rubber and asphalt, so that the modifier is evenly dispersed in the asphalt matrix to form a preliminary modified asphalt system.
[0012] Preferably, in the composite aqueous phase stage, 30 parts of deionized water are added to another mixing tank, followed by 0.4 parts of composite stabilizer and 0.3 parts of composite anti-aging agent, and the mixture is stirred at 75°C and 600 r / min for 30 min. Then, the emulsifier aqueous solution prepared in the raw material pretreatment stage was added, and the mixture was stirred for 15 minutes to ensure uniform fusion of all components, thus obtaining a composite aqueous phase.
[0013] Preferably, in the stepwise emulsification stage, the preliminary modified asphalt system and the composite aqueous phase are introduced into the colloid mill through a heat-insulated feed pipe equipped with real-time temperature monitoring. The asphalt temperature is controlled at 130-135℃ and the aqueous phase temperature at 68-72℃. The gap of the colloid mill is adjusted to 0.12-0.15mm, and the material throughput rate is 4.5 parts / min. An online viscosity monitoring module is set at the outlet of the colloid mill to provide real-time feedback on viscosity data. If the viscosity deviates from the optimal range of 200-300mPa·s, the feed temperature or the gap of the colloid mill is adjusted through the intelligent control system to correct the deviation, thereby obtaining the primary emulsified asphalt. Online viscosity monitoring uses a rotary viscometer with a measurement range of 50-1000 mPa·s and an accuracy of ±5 mPa·s; online particle size monitoring uses a laser particle size analyzer with a testing range of 0.1-100 μm and a particle size measurement accuracy of ±0.1 μm.
[0014] The primary emulsified asphalt is introduced into a high-pressure homogenizer, and 0.6 parts of silane coupling agent are added through a high-precision metering pump. The pressure feedback adjustment system is turned on, and the initial pressure is set to 35 MPa. The pressure is dynamically adjusted to 40-45 MPa based on online particle size monitoring data. The temperature is maintained at 60-65℃, and the processing time is 12 minutes to make the emulsified asphalt particles have a uniform particle size distribution.
[0015] Preferably, in the cooling and maturation stage, the secondary emulsified asphalt is introduced into a cooling tank equipped with stirring and temperature control. The stirring rate is set to 150 r / min. First, the temperature is lowered to 50°C at a rate of 4°C / min and held for 20 min to make the internal temperature of the system uniform. Then, the temperature is lowered to 30°C at a rate of 2°C / min and held for 15 min. Finally, the temperature is slowly lowered to 25°C at a rate of 1°C / min. Subsequently, the asphalt is allowed to stand and mature at 25°C for 36 h to finally form a modified emulsified asphalt semi-finished product.
[0016] Preferably, the finished product testing stage involves comprehensive performance testing of the matured modified emulsified asphalt semi-finished product. The core testing indicators include: average particle size ≤ 4μm, 5d segregation degree ≤ 2%, storage period ≥ 6 months, penetration 60-80, softening point ≥ 55℃, and low temperature ductility at -10℃ ≥ 30cm. Anti-aging performance testing is also added. If the test indicators do not meet the standards, make targeted adjustments; if the particle size is too large, return it to the high-pressure homogenizer and appropriately increase the pressure by 5-10MPa for reprocessing; if the segregation exceeds the standard, add 0.05-0.1 parts of composite stabilizer precisely; if the anti-aging performance is insufficient, add 0.05 parts of composite anti-aging agent to obtain the finished modified emulsified asphalt.
[0017] The finished emulsified asphalt exhibits a slow-crack, fast-setting demulsification rate and shows no sticking to wheels or stringing when tested according to relevant methods. Its adhesion to aggregates is grade ≥4, and at 23℃, the bond strength between asphalt and concrete is ≥1.0MPa and the shear strength is ≥0.8MPa.
[0018] Storage stability is determined by a 48-hour segregation test, with the difference in softening points between the upper and lower layers ≤ 2.5℃. If stratification occurs during storage, the particle size and viscosity must be retested after stirring, and the product can only be used after meeting the standards.
[0019] This invention also provides a modified emulsified asphalt, prepared by the above-described preparation method, comprising the following parts by weight of materials: The composition includes 65-75 parts base asphalt, 5.0-6.0 parts composite modifier, 1.5-2.5 parts cationic emulsifier, 0.2-0.4 parts penetration enhancer, 0.3-0.5 parts composite stabilizer, 0.2-0.4 parts composite anti-aging agent, 0.1-0.3 parts accelerator, 0.5-0.7 parts silane coupling agent, and 40-50 parts deionized water. The composite modifier is composed of 2.9-3.4 parts of epoxy-modified styrene-butadiene rubber latex, 1.8-2.1 parts of graphene oxide-silica hybrid, and 0.4-0.5 parts of modified polyvinyl alcohol; The modified polyvinyl alcohol is formaldehyde-modified polyvinyl alcohol, and its preparation process is as follows: dissolve polyvinyl alcohol in deionized water at 80-90℃ to prepare a solution with a mass fraction of 10%-15%; add formaldehyde at 3%-5% of the mass of polyvinyl alcohol, adjust the pH to 2-3 with hydrochloric acid, and react at 70-80℃ for 1-1.5h; after cooling, adjust the pH to 7-8 with sodium hydroxide, filter, wash, and dry at 60-70℃ to obtain the product.
[0020] The composite stabilizer is composed of 0.2-0.3 parts of walnut green husk biochar-modified organic bentonite and 0.1-0.2 parts of hydroxyethyl cellulose; The preparation process of the walnut green husk biochar modified organic bentonite is as follows: walnut green husks are washed and dried, pyrolyzed at 500-600℃ for 2-3 hours under a nitrogen atmosphere, cooled, and ground through a 100-mesh sieve to obtain walnut green husk biochar; organic bentonite and walnut green husk biochar are weighed at a mass ratio of 10:1-1.5, 20-25 times the mass of deionized water is added, and the mixture is stirred and modified at 60-70℃ and 400-600 r / min for 1.5-2 hours; after filtration, the precipitate is dried at 100-110℃ for 6-8 hours, and then pulverized through a 150-mesh sieve to obtain the final product.
[0021] The composite anti-aging agent is composed of 0.1-0.2 parts of 2,6-di-tert-butyl-p-cresol and 0.1-0.2 parts of boronite powder; The boron ferroore powder in the composite anti-aging agent needs to be pretreated: after crushing the boron ferroore powder, it is passed through a 300-mesh sieve, soaked in a 5%-8% hydrochloric acid solution for 1-2 hours, washed with deionized water until neutral, and dried at 80-100℃ for 4-6 hours before use.
[0022] The preparation method of the composite anti-aging agent is as follows: Weigh 2,6-di-tert-butyl-p-cresol and pretreated boron iron ore powder according to the ratio, place them in a mixing tank, and stir for 10-15 minutes at 50-60℃ and 300-400r / min until the material is evenly dispersed and there is no obvious agglomeration.
[0023] The cationic emulsifier is dodecyltrimethylammonium chloride, the accelerator is triethanolamine, and the silane coupling agent is KH-560.
[0024] The beneficial effects of this invention are as follows: 1. The composite modifier of this invention integrates flexible reinforcement, rigid support, and interface modification components. It utilizes the synergistic effect of the reaction between epoxy groups and asphalt active sites, and combined with the gradient shear strategy and the catalytic effect of the accelerator, the modifier is uniformly dispersed in the asphalt matrix, avoiding the thermal degradation of the modifier caused by traditional high-temperature and long-term stirring. Vacuum low-temperature pretreatment reduces asphalt thermal aging. The final product can simultaneously meet the requirements of high-temperature deformation resistance and low-temperature crack resistance, adapting to heavy traffic and complex climatic conditions, and improving the load-bearing capacity and fatigue resistance of roads.
[0025] 2. This invention utilizes the synergistic design of composite stabilizers, taking advantage of porous adsorption characteristics and swelling stability, to inhibit asphalt particle segregation, flocculation, and sedimentation without excessive addition, thus extending the storage period. The interfacial bridging effect of the silane coupling agent during the stepwise emulsification process further optimizes the system stability. Combined with the use of penetration enhancers, it ensures the adhesion strength between emulsified asphalt and aggregates, making the road surface layer and base layer more tightly bonded, improving overall strength, water damage resistance, and durability, and reducing early-stage defects and later maintenance costs.
[0026] 3. The present invention employs relatively low-temperature processes in the raw material pretreatment and modified premixing stages, avoiding the high energy consumption and asphalt thermal aging problems caused by traditional high-temperature processes; the gradient cooling and segmented heat preservation strategies eliminate temperature stress and prevent asphalt particles from re-agglomerating; at the same time, online viscosity monitoring, dynamic pressure adjustment, and targeted adjustment mechanisms for finished products ensure the uniformity and stability of product performance; the synergistic effect of composite anti-aging agents enhances the product's resistance to thermal and photo-oxidative aging. Attached Figure Description
[0027] Figure 1 This is an overall flow chart of the preparation method of the present invention; Figure 2 This is a flowchart illustrating the preparation process of the pre-dispersion of the composite modifier of the present invention. Figure 3 This is a flowchart of the stepwise emulsification core process of the present invention. Detailed Implementation
[0028] The following will be based on embodiments of the present invention. Figures 1 to 3 As shown, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. Example 1
[0029] A modified emulsified asphalt formulation composition (parts by weight) The composition includes 65-75 parts of base asphalt, 5.0-6.0 parts of composite modifier, 1.5-2.5 parts of cationic emulsifier, 0.2-0.4 parts of penetration enhancer, 0.3-0.5 parts of composite stabilizer, 0.2-0.4 parts of composite anti-aging agent, 0.1-0.3 parts of accelerator, 0.5-0.7 parts of silane coupling agent, and 40-50 parts of deionized water; wherein the penetration enhancer is 5-benzotriazolyl-4-hydroxy-3-isobutylbenzenesulfonic acid.
[0030] The composite modifier consists of 2.9-3.4 parts of epoxy-modified styrene-butadiene rubber latex, 1.8-2.1 parts of graphene oxide-silica hybrid, and 0.4-0.5 parts of modified polyvinyl alcohol.
[0031] The epoxy-modified styrene-butadiene rubber latex has a solid content of 20%-25%, an epoxy degree of 11%-23%, and rubber particles with a particle size of 0.5-2μm in the latex, with no obvious agglomeration, ensuring compatibility with the asphalt matrix and the modification effect.
[0032] When preparing the composite modifier, first add epoxy-modified styrene-butadiene rubber latex to a portion of the aqueous phase and stir for 5 minutes. Then, add graphene oxide-silica hybrid and modified polyvinyl alcohol in sequence and continue stirring for 10 minutes to ensure that each component is uniformly dispersed without stratification.
[0033] The composite stabilizer is composed of 0.2-0.3 parts of walnut green husk biochar-modified organic bentonite and 0.1-0.2 parts of hydroxyethyl cellulose; The composite anti-aging agent is composed of 0.1-0.2 parts of 2,6-di-tert-butyl-p-cresol and 0.1-0.2 parts of boronite powder; Weigh 2,6-di-tert-butyl-p-cresol and pretreated boron iron ore powder according to the formula, place them in a mixing tank, and stir for 10-15 minutes at 50-60℃ and 300-400r / min until the material is evenly dispersed without obvious agglomeration, and the composite anti-aging agent is obtained. The cationic emulsifier is dodecyltrimethylammonium chloride, the accelerator is triethanolamine, and the silane coupling agent is KH-560.
[0034] A method for preparing modified emulsified asphalt includes the following specific steps: In the raw material pretreatment stage, 70 parts of base asphalt with a penetration of 60-80 are selected and placed in a heating kettle equipped with a vacuum devolatilization device. This device can quickly extract volatile components through a negative pressure environment and treat the asphalt at a constant temperature of 125-135℃ and a vacuum of -0.06~-0.08MPa for 35 minutes. This not only accelerates the removal of moisture and light volatiles and effectively avoids the bubble defects caused by the presence of moisture during the subsequent emulsification process, but also significantly reduces the thermal aging of asphalt due to the lower treatment temperature of 5-10℃ compared with the traditional process, ultimately obtaining pretreated asphalt with stable performance.
[0035] A composite modifier consisting of 3 parts epoxy-modified styrene-butadiene rubber latex, 2 parts graphene oxide-silica hybrid, and 0.5 parts modified polyvinyl alcohol was selected. To prepare the pre-dispersion of the composite modifier, the graphene oxide-silica hybrid was first added to 10 parts deionized water and ultrasonically dispersed for 20 minutes. Then, the epoxy-modified styrene-butadiene rubber latex and modified polyvinyl alcohol were added, and stirring was continued for 20 minutes to break up the aggregates using ultrasonic cavitation. The graphene oxide-silica hybrid was prepared by covalent bonding with KH-550 silane coupling agent, which enhanced the bonding stability of the two components. Then, epoxy-modified styrene-butadiene rubber latex and modified polyvinyl alcohol are added and placed in a mixing tank and stirred at 65°C and 900 r / min for 20 min to form a stable pre-dispersion of the modifier. Through the reaction of epoxy groups with the active sites of asphalt and the layered support structure of the hybrid, the synergistic effect of flexible reinforcement and rigid support is enhanced.
[0036] Prepare 12 parts of emulsifier aqueous solution, consisting of 2 parts cationic emulsifier, 0.3 parts penetration enhancer, and 9.7 parts deionized water. Stir and dissolve at 55℃ until transparent to ensure that the emulsifier is completely dissociated into ionic state. The addition of penetration enhancer can further improve the penetration ability and adhesion of subsequent emulsified asphalt to the aggregate surface. The cationic emulsifier is dodecyltrimethylammonium chloride; the penetration enhancer is 5-benzotriazolyl-4-hydroxy-3-isobutylbenzenesulfonic acid, which can reduce the surface tension of emulsified asphalt.
[0037] The base asphalt is 70# road petroleum asphalt, with a penetration of 60-80 (0.1mm) at 25℃, a softening point of 45-50℃, a ductility of ≥100cm at 10℃, and a wax content of ≤3%, ensuring the stability of the raw material performance.
[0038] Boron-iron ore powder pretreatment: After crushing, pass through a 300-mesh sieve, soak in 5%-8% hydrochloric acid solution for 1-2 hours, wash with deionized water until neutral, and dry at 80-100℃ for 4-6 hours for later use to remove impurities and improve activity.
[0039] The emulsifier should be of type with an HLB value of 12-16, an active ingredient content of ≥95%, good water solubility at 25℃ without stratification, and ensure emulsification effect.
[0040] Hydroxyethyl cellulose must meet the following requirements: viscosity of 1500-3000 mPa·s at 25℃ and 2% by mass of aqueous solution, degree of substitution 2.0-2.5, whiteness ≥85%, and enhance system stability.
[0041] In the modified premixing stage, the prepared modifier predispersed liquid is slowly added to the pretreated asphalt, and the feeding rate is strictly controlled at 0.8 parts / min. This rate can accurately avoid the secondary agglomeration of the modifier due to excessive local concentration. The asphalt temperature is maintained at 135-140℃ to ensure good fluidity and facilitate the uniform diffusion of the modifier.
[0042] The high-speed shearing machine employs a gradient shearing strategy. First, it is sheared at 2500 r / min for 10 minutes for initial dispersion to break up large agglomerates. Then, the temperature is increased to 140-145℃ and sheared at 3500 r / min for 15 minutes to refine the small agglomerates through high shear force. At the same time, 0.2 parts of accelerator are added. The accelerator selected is triethanolamine, which can catalyze the reaction rate between epoxy groups and the active sites of asphalt, accelerate the bonding between epoxy-modified styrene-butadiene rubber and asphalt, and finally make the modifier uniformly dispersed in the asphalt matrix to form a stable preliminary modified asphalt system and improve interfacial compatibility.
[0043] The specific details of the composite aqueous phase stage are as follows: In another mixing tank, 30 parts of deionized water were added as the base carrier, followed by 0.4 parts of composite stabilizer and 0.3 parts of composite anti-aging agent. The mixture was stirred at 75°C and 600 r / min for 30 min until the material was completely dissolved and dispersed and the system was free of obvious particles. The composite stabilizer consisted of 0.25 parts of walnut green husk biochar-modified organic bentonite and 0.15 parts of hydroxyethyl cellulose. The porous structure of the biochar could adsorb organic bentonite particles and enhance dispersibility. The composite anti-aging agent consisted of 0.15 parts of 2,6-di-tert-butyl-p-cresol and 0.15 parts of boronite powder. The two components could form a synergistic anti-aging effect.
[0044] Subsequently, the emulsifier aqueous solution prepared in the raw material pretreatment stage is added, and the mixture is stirred for another 15 minutes to ensure uniform fusion of all components, resulting in a composite aqueous phase with excellent stability. Through the synergistic effect of the porous adsorption characteristics of biochar and the bentonite stability of organic bentonite, the storage stability can be improved while reducing the amount of stabilizer used. The composite anti-aging agent can simultaneously resist thermal oxidative and photo-oxidative aging.
[0045] When preparing the aqueous phase, deionized water is added and the pH value is adjusted to 2-3 with hydrochloric acid. The pH value is monitored in real time during the emulsification process, and the fluctuation range is controlled within ±0.2 to avoid pH abnormalities affecting the stability of the emulsion system.
[0046] In the stepwise emulsification stage, the pre-modified asphalt system and the composite aqueous phase are introduced into the colloid mill through insulated feed pipes equipped with real-time temperature monitoring. The insulated pipes prevent temperature loss during material transport. The asphalt temperature is strictly controlled at 130-135℃ and the aqueous phase temperature at 68-72℃. This temperature ratio ensures that the viscosity ratio of asphalt to aqueous phase is within the optimal range. The gap of the colloid mill is adjusted to 0.12-0.15mm, and the material throughput rate is 4.5 parts / min. An online viscosity monitoring module is installed at the outlet of the colloid mill to provide real-time feedback on viscosity data. If the viscosity deviates from the optimal range of 200-300mPa·s, the intelligent control system immediately adjusts the feed temperature or the gap of the colloid mill to correct the deviation, ensuring the uniform dispersion of the primary emulsified asphalt and obtaining a stable quality primary emulsified asphalt.
[0047] Colloid mill operating parameters: operating speed 4000-5000 r / min, maintain stable speed during shearing process and avoid frequent adjustments.
[0048] Intelligent adjustment logic: When the online viscosity is higher than 300 mPa·s, the aqueous phase temperature is increased by 2-3℃ or the colloid mill gap is increased by 0.01-0.02 mm; when the viscosity is lower than 200 mPa·s, the aqueous phase temperature is decreased by 2-3℃ or the colloid mill gap is decreased by 0.01-0.02 mm.
[0049] Monitoring equipment requirements: Online viscosity monitoring uses a rotary viscometer with a measurement range of 50-1000 mPa·s and an accuracy of ±5 mPa·s; online particle size monitoring uses a laser particle size analyzer with a testing range of 0.1-100 μm and an accuracy of ±0.1 μm.
[0050] The primary emulsified asphalt is introduced into a high-pressure homogenizer, and 0.6 parts of silane coupling agent (KH-560) are precisely added using a high-precision metering pump. The pressure feedback regulation system is activated, with the initial pressure set at 35 MPa. Based on online particle size monitoring data (target particle size ≤ 4 μm), the pressure is dynamically adjusted to 40-45 MPa. The temperature is maintained at 60-65℃ to prevent decomposition of the coupling agent, and the processing time is 12 minutes to ensure sufficient reaction. The deep crushing effect of high-pressure homogenization refines the particles, and combined with the interfacial bridging effect of the coupling agent, the particle size distribution of the emulsified asphalt is made more uniform, forming a stable core-shell structure and improving the overall stability of the system.
[0051] In the cooling and maturation stage, the secondary emulsified asphalt is introduced into a cooling tank equipped with agitation and precise temperature control. The agitation rate is set to 150 r / min to assist in temperature conduction. A three-stage gradient cooling method is adopted: first, the temperature is lowered to 50℃ at a rate of 4℃ / min and held for 20 minutes to make the internal temperature of the system uniform and eliminate the internal stress caused by local temperature differences; then, the temperature is lowered to 30℃ at a rate of 2℃ / min and held for 15 minutes to allow the system to gradually adapt to the temperature change; finally, the temperature is slowly lowered to room temperature (25℃) at a rate of 1℃ / min, which can effectively avoid the asphalt particles from re-agglomerating due to a sudden drop in temperature.
[0052] Subsequently, the mixture was left to stand and mature at room temperature for 36 hours to allow the emulsifier and coupling agent to be fully adsorbed on the surface of the asphalt particles and reach a balanced state, so that the emulsion system was completely stable and a modified emulsified asphalt semi-finished product with uniform performance was finally formed.
[0053] The curing process is carried out at room temperature of 20-30℃, avoiding direct sunlight and drastic temperature fluctuations. The criteria for judging adsorption equilibrium are: continuous sampling and testing for 3 hours, the particle size variation coefficient of emulsified asphalt particles ≤1%, and the viscosity fluctuation value of the system ≤5mPa·s. Curing can be ended after the standard is met.
[0054] The finished product testing stage involves comprehensive performance testing of the matured modified emulsified asphalt semi-finished product. The testing adopts the test methods specified in the national standards. The core test indicators include: average particle size ≤ 4μm to ensure uniform dispersion; 5-day segregation degree ≤ 2% to ensure transportation and storage performance; storage period ≥ 6 months; penetration (25℃) 60-80 (0.1mm); softening point ≥ 55℃; low-temperature ductility at -10℃ ≥ 30cm. At the same time, anti-aging performance testing is added, with softening point increase ≤ 8℃ and ductility retention rate ≥ 70% after aging, to evaluate long-term use performance.
[0055] If the test indicators do not meet the standards, targeted and precise adjustments are made: if the particle size is too large, return it to the high-pressure homogenizer and appropriately increase the pressure by 5-10 MPa for reprocessing; if the segregation exceeds the standard, precisely add 0.05-0.1 parts of composite stabilizer; if the anti-aging performance is insufficient, add 0.05 parts of composite anti-aging agent. After ensuring that all indicators meet the relevant standard requirements, a high-performance modified emulsified asphalt product is obtained.
[0056] The product has a shelf life of more than 6 months from the date of production. Storage conditions: 5-45℃ in a cool and ventilated environment, avoid exposure to sunlight and freezing at low temperatures; stir once a week during storage, at a speed of 300r / min for 5min.
[0057] Table 1: Performance Test Data of Example 1 Example 2
[0058] Formula composition (parts by weight) The composition includes 65 parts of base asphalt, 5.0 parts of composite modifier (2.5 parts of epoxy-modified styrene-butadiene rubber latex, 1.5 parts of graphene oxide-silica hybrid, and 0.4 parts of modified polyvinyl alcohol), 1.5 parts of cationic emulsifier (dodecyltrimethylammonium chloride), 0.2 parts of penetration enhancer (5-benzotriazolyl-4-hydroxy-3-isobutylbenzenesulfonic acid), 0.3 parts of composite stabilizer (0.2 parts of walnut green husk biochar-modified organic bentonite and 0.1 parts of hydroxyethyl cellulose), 0.2 parts of composite anti-aging agent (0.1 parts of 2,6-di-tert-butyl-p-cresol and 0.1 parts of pretreated boron iron ore powder), 0.1 parts of accelerator (triethanolamine), 0.5 parts of silane coupling agent (KH-560), and 40 parts of deionized water.
[0059] Preparation steps Raw material pretreatment stage: 65 parts of base asphalt were selected and placed in a heating kettle equipped with a vacuum devolatilization device. The mixture was kept at 125℃ and -0.06MPa vacuum for 30 minutes to remove moisture and light volatiles, thus obtaining pretreated asphalt. 5.0 parts of composite modifier were taken. First, 1.5 parts of graphene oxide-silica hybrid were added to 8 parts of deionized water and ultrasonically dispersed at 280W for 15 minutes. Then, 2.5 parts of epoxy-modified styrene-butadiene rubber latex and 0.4 parts of modified polyvinyl alcohol were added and stirred at 60℃ and 800r / min for 15 minutes to prepare a pre-dispersion liquid. 12 parts of an aqueous solution containing 1.5 parts of cationic emulsifier and 0.2 parts of penetration enhancer were prepared and stirred at 50℃ until transparent.
[0060] Modified premixing stage: Add the predispersed modifier liquid to the pretreated asphalt at a rate of 0.6 parts / min, and maintain the asphalt temperature at 135℃; turn on the high-speed shearing machine, first shear at 2000 r / min for 8 min, then raise the temperature to 140℃ and shear at 3000 r / min for 12 min, while adding 0.1 parts of accelerator to form a preliminary modified asphalt system.
[0061] Composite aqueous phase stage: Add 25 parts of deionized water to a mixing tank, then add 0.3 parts of composite stabilizer and 0.2 parts of composite anti-aging agent in sequence. Stir at 70℃ and 500r / min for 25min. Then add the above emulsifier aqueous solution and continue stirring for 10min to obtain the composite aqueous phase.
[0062] Stepwise emulsification stage: The pre-modified asphalt system and the composite aqueous phase are separately introduced into a colloid mill under controlled temperature. The asphalt temperature is controlled at 130℃ and the aqueous phase temperature at 65℃. The colloid mill gap is 0.10mm, the material throughput rate is 4.0 parts / min, and the online viscosity is controlled at 200-300mPa·s. 0.5 parts of silane coupling agent are added to the primary emulsion product and introduced into a high-pressure homogenizer. The initial pressure is 30MPa, which is dynamically adjusted to 40MPa. The temperature is maintained at 60℃ and high-pressure homogenization is performed for 10min to form an emulsion system.
[0063] Cooling and maturation stage: The secondary emulsified product is introduced into a cooling tank, the stirring rate is set to 120 r / min, and the gradient cooling program is as follows: first, the temperature is lowered to 45℃ at a rate of 3℃ / min and held for 15 min, then the temperature is lowered to 28℃ at a rate of 1℃ / min and held for 10 min, and finally the temperature is lowered to 23℃ at a rate of 0.5℃ / min; the product is then allowed to stand and mature at 23℃ for 30 h to obtain a semi-finished product.
[0064] Finished product testing stage: The performance of the semi-finished product is tested, and the finished modified emulsified asphalt is obtained after the indicators meet the standards.
[0065] Table 2: Performance Test Data of Example 2 Example 3
[0066] Formula composition (parts by weight) The composition includes 75 parts of base asphalt, 6.0 parts of composite modifier (3.5 parts of epoxy-modified styrene-butadiene rubber latex, 2.5 parts of graphene oxide-silica hybrid, and 0.6 parts of modified polyvinyl alcohol), 2.5 parts of cationic emulsifier (dodecyltrimethylammonium chloride), 0.4 parts of penetration enhancer (5-benzotriazolyl-4-hydroxy-3-isobutylbenzenesulfonic acid), 0.5 parts of composite stabilizer (0.3 parts of walnut green husk biochar-modified organic bentonite and 0.2 parts of hydroxyethyl cellulose), 0.4 parts of composite anti-aging agent (0.2 parts of 2,6-di-tert-butyl-p-cresol and 0.2 parts of pretreated boron ore powder), 0.3 parts of accelerator (triethanolamine), 0.7 parts of silane coupling agent (KH-560), and 50 parts of deionized water.
[0067] Preparation steps Raw material pretreatment stage: 75 parts of base asphalt were selected and placed in a heating kettle equipped with a vacuum devolatilization device. The mixture was kept at 135℃ and -0.08MPa vacuum for 40 minutes to remove moisture and light volatiles, thus obtaining pretreated asphalt. 6.0 parts of composite modifier were taken. First, 2.5 parts of graphene oxide-silica hybrid were added to 12 parts of deionized water and ultrasonically dispersed at 320W for 25 minutes. Then, 3.5 parts of epoxy-modified styrene-butadiene rubber latex and 0.6 parts of modified polyvinyl alcohol were added and stirred at 70℃ and 1000r / min for 25 minutes to prepare a pre-dispersion liquid. 18 parts of an aqueous solution containing 2.5 parts of cationic emulsifier and 0.4 parts of penetration enhancer were prepared and stirred at 60℃ until transparent.
[0068] Modified premixing stage: Add the predispersed modifier liquid to the pretreated asphalt at a rate of 1.0 parts / min, and maintain the asphalt temperature at 145℃; turn on the high-speed shearing machine, first shear at 3000 r / min for 12 min, then raise the temperature to 145℃ and shear at 4000 r / min for 18 min, while adding 0.3 parts of accelerator to form a preliminary modified asphalt system.
[0069] Composite aqueous phase stage: Add 35 parts of deionized water to a mixing tank, then add 0.5 parts of composite stabilizer and 0.4 parts of composite anti-aging agent in sequence. Stir at 80℃ and 700r / min for 35min. Then add the above emulsifier aqueous solution and continue stirring for 20min to obtain the composite aqueous phase.
[0070] Stepwise emulsification stage: The pre-modified asphalt system and the composite aqueous phase are separately introduced into a colloid mill under controlled temperature. The asphalt temperature is controlled at 135℃ and the aqueous phase temperature at 75℃. The colloid mill gap is 0.15mm, the material throughput rate is 5.0 parts / min, and the online viscosity is controlled at 200-300mPa·s. 0.7 parts of silane coupling agent are added to the primary emulsion product and introduced into a high-pressure homogenizer. The initial pressure is 40MPa, which is dynamically adjusted to 45MPa. The temperature is maintained at 65℃ and high-pressure homogenization is performed for 15min to form an emulsion system.
[0071] Cooling and maturation stage: The secondary emulsified product is introduced into a cooling tank, the stirring rate is set to 180 r / min, and the gradient cooling program is as follows: first, the temperature is lowered to 55℃ at a rate of 5℃ / min and held for 25 min, then the temperature is lowered to 32℃ at a rate of 3℃ / min and held for 20 min, and finally the temperature is lowered to 27℃ at a rate of 1.5℃ / min; the product is then allowed to stand and mature at 27℃ for 42 h to obtain the semi-finished product.
[0072] Finished product testing stage: The performance of the semi-finished product is tested, and the finished modified emulsified asphalt is obtained after the indicators meet the standards.
[0073] Table 3: Performance Test Data of Example 3
[0074] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0075] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a modified emulsified asphalt, characterized by, The method comprises the following specific steps: The raw material pretreatment stage: vacuum low-temperature pretreatment is performed on the base asphalt to remove water and light volatile components; a composite modifier containing a flexible reinforcing component, a rigid support hybrid and an interface modification component is prepared into a pre-dispersion liquid through ultrasonic dispersion and constant temperature stirring; An aqueous solution containing an emulsifier and a penetration enhancer is prepared and the emulsifier is ensured to be dissociated; The modified premixing stage: the modifier pre-dispersion liquid is added to the pretreated asphalt, a gradient shear strategy is adopted and a promoter is added, so that the modifier is uniformly dispersed in the asphalt matrix to form a preliminary modified asphalt system; The composite aqueous phase stage: deionized water is used as a carrier, a composite stabilizer and a composite anti-aging agent are sequentially added and stirred and dispersed, and then the emulsifier aqueous solution is mixed to prepare a composite aqueous phase; The step-by-step emulsification stage: the preliminary modified asphalt system and the composite aqueous phase are respectively introduced into a colloid mill for primary emulsification, the temperature, gap and online viscosity are monitored in real time to modify the parameters to ensure the uniformity of the product; the silane coupling agent is added to the primary emulsification product, and secondary emulsification is performed through a high-pressure homogenizer, the pressure is dynamically adjusted to control the degree of particle refinement, and an emulsified system is formed; The cooling and curing stage: the secondary emulsification product is gradually cooled in a multi-stage gradient cooling mode, and is subjected to segmented heat preservation to eliminate temperature stress; the emulsifier and the coupling agent are adsorbed and balanced through room temperature standing and curing to form a semi-finished product; The finished product detection stage: the semi-finished product after curing is subjected to detection of dispersibility, stability and road core performance, and targeted adjustment is performed on unqualified items to obtain a qualified finished product.
2. The method of preparing a modified emulsified asphalt according to claim 1, characterized by, In the raw material pretreatment stage, 65-75 parts of base asphalt are selected, and constant temperature treatment is performed at 125-135 DEG C and under a vacuum condition of -0.06 to -0.08 MPa for 30-40 min; 5.0-6.0 parts of a composite modifier are selected, the rigid support hybrid is first added to 8-12 parts of deionized water and ultrasonic dispersion is performed for 15-25 min, and then the remaining components are added and stirred at 60-70 DEG C and a rotation speed of 800-1000 r / min for 15-25 min to prepare a pre-dispersion liquid; 12-18 parts of an aqueous solution containing an emulsifier and a penetration enhancer is prepared, and stirring and dissolution are performed at 50-60 DEG C until the solution is transparent.
3. The method of claim 2, wherein the modified emulsified asphalt is prepared by adding the modified emulsified asphalt to the asphalt mixture. In the modified premixing stage, the feeding rate of the modifier pre-dispersion liquid is 0.6-1.0 parts / min, and the asphalt temperature is maintained at 135-145 DEG C; the gradient shear strategy specifically comprises the following steps: shear is first performed at a rotation speed of 2000-3000 r / min for 8-12 min, then the temperature is increased to 140-145 DEG C, shear is performed at a rotation speed of 3000-4000 r / min for 12-18 min, and the amount of the promoter added is 0.1-0.3 parts.
4. The method of claim 3, wherein the modified emulsified asphalt is prepared by adding the polyphenol compound to the emulsified asphalt. In the composite aqueous phase stage, the amount of deionized water is 25-35 parts, 0.3-0.5 parts of a composite stabilizer and 0.2-0.4 parts of a composite anti-aging agent are sequentially added, stirring is performed at 70-80 DEG C and a rotation speed of 500-700 r / min for 25-35 min, and then the emulsifier aqueous solution is added and stirring is continued for 10-20 min.
5. The method of claim 4, wherein the modified emulsified asphalt is prepared by adding the polyphenol to the asphalt emulsion. The specific parameters for the stepwise emulsification stage are as follows: During the first-stage emulsification, the asphalt temperature is controlled at 130-135℃, the aqueous phase temperature is 65-75℃, the colloid mill gap is 0.10-0.15mm, the material throughput rate is 4.0-5.0 parts / min, and the online viscosity is controlled at 200-300mPa·s; During the second-stage emulsification, the amount of silane coupling agent added is 0.5-0.7 parts, the initial pressure is 30-40MPa, dynamically adjusted to 40-45MPa, the temperature is maintained at 60-65℃, and the high-pressure homogenization time is 10-15min.
6. The method of preparing a modified emulsified asphalt according to claim 5, characterized by, During the cooling and maturation stage, the stirring rate is set to 120-180 r / min, and the gradient cooling program is as follows: first, the temperature is lowered to 45-55℃ at a rate of 3-5℃ / min and held for 15-25 min; then, the temperature is lowered to 28-32℃ at a rate of 1-3℃ / min and held for 10-20 min; finally, the temperature is lowered to 23-27℃ at a rate of 0.5-1.5℃ / min; the static maturation temperature is 23-27℃, and the time is 30-42 h.
7. The method of claim 6, wherein the modified emulsified asphalt is prepared by adding the polyphenol to the asphalt emulsion. The core indicators for finished product testing are: average particle size ≤ 4μm, 5-day segregation ≤ 2%, storage period ≥ 6 months, penetration 60-80, softening point ≥ 55℃, low-temperature ductility at -10℃ ≥ 30cm, softening point increment after aging ≤ 8℃, and low-temperature ductility retention rate at -10℃ ≥ 70%. The penetration test temperature is 25℃, and the unit is 0.1mm. The adjustment plan for non-compliance is as follows: if the particle size is too large, return it to the high-pressure homogenizer and increase the pressure by 5-10MPa for reprocessing; if the segregation exceeds the standard, add 0.05-0.1 parts of composite stabilizer; if the anti-aging performance is insufficient, add 0.05 parts of composite anti-aging agent.
8. A modified emulsified asphalt produced on the basis of the production method according to claim 7, characterized in that Composed of the following parts by weight: The composition includes 65-75 parts base asphalt, 5.0-6.0 parts composite modifier, 1.5-2.5 parts cationic emulsifier, 0.2-0.4 parts penetration enhancer, 0.3-0.5 parts composite stabilizer, 0.2-0.4 parts composite anti-aging agent, 0.1-0.3 parts accelerator, 0.5-0.7 parts silane coupling agent, and 40-50 parts deionized water. The composite modifier is composed of 2.9-3.4 parts of epoxy-modified styrene-butadiene rubber latex, 1.8-2.1 parts of graphene oxide-silica hybrid, and 0.4-0.5 parts of modified polyvinyl alcohol; The composite stabilizer is composed of 0.2-0.3 parts of walnut green husk biochar-modified organic bentonite and 0.1-0.2 parts of hydroxyethyl cellulose; The composite anti-aging agent is composed of 0.1-0.2 parts of 2,6-di-tert-butyl-p-cresol and 0.1-0.2 parts of boronite powder; The cationic emulsifier is dodecyltrimethylammonium chloride, the accelerator is triethanolamine, and the silane coupling agent is KH-560.
